PENERAPAN ISLAMISASI SAINS AL-FARUQI DALAM SILABUS BIOLOGI. - Rabbaniyah, Jundiyah; Handrianto, Budi; Sastra, Ahmad (Tawazun: Jurnal Pendidikan Islam, 2020)
Many teachers in Islamic schools agree with the Islamic learning device, but the teachers do not fully know the steps to Islamize the learning device. The science Islamization is very important in every process of education in schools. Especially teachers, students, learning tools must be Islamized. In order that it can form humans who have faith, piety, and noble character. This study aims to determine the Islamization steps of science according to al-Faruqi and its application in the biological syllabus. This study is a qualitative study using the literature studies to describe and explain the Islamization thought of al-Faruqi science about the steps of Islamizing of science. Apply it in the biology syllabus of class IX middle school. This study uses a descriptive approach whose data is obtained through analysis. The result of this study are Islamization thoughts of al-Faruqi science in the Islamization steps of science by mastering modern scientific disciplines, mastering the heritage of Muslim thought, mastering Islamic treasures, Islamic treasures must be combined with the achievements and results of modern science, and reformulating modern scientific disciplines in Islamic view and spread it. Then apply it to the Biology syllabus of class IX SMP based on the science Islamization. Abstrak Banyak guru di sekolah Islam setuju dengan perangkat pembelajaran Islam, tetapi para guru tidak sepenuhnya tahu langkah-langkah untuk mengislamkan perangkat pembelajaran. Ilmu islamisasi sangat penting dalam setiap proses pendidikan di sekolah. Terutama guru, siswa, dan alat pembelajaran harus diislamkan. Agar dapat membentuk manusia yang beriman, saleh, dan berkarakter luhur. Penelitian ini bertujuan untuk menentukan langkah-langkah Islamisasi sains menurut al-Faruqi dan penerapannya dalam silabus biologi. Penelitian ini adalah penelitian kualitatif dengan menggunakan studi literatur untuk menggambarkan dan menjelaskan pemikiran islamisasi sains al-Faruqi tentang langkah-langkah islamisasi sains. Menerapkannya dalam silabus biologi kelas IX sekolah menengah. Penelitian ini menggunakan pendekatan deskriptif yang datanya diperoleh melalui analisis. Hasil dari penelitian ini adalah pemikiran Islamisasi sains al-Faruqi dalam langkah-langkah sains Islamisasi dengan menguasai disiplin ilmu modern, menguasai warisan pemikiran Muslim, menguasai khazanah Islam, khazanah Islam harus dikombinasikan dengan pencapaian dan hasil sains modern, dan merumuskan kembali disiplin ilmu modern dalam pandangan Islam dan menyebarkannya. Kemudian menerapkannya pada silabus Biologi kelas IX SMP berdasarkan ilmu keislaman.